Pengaruh Peran Penerapan Digitalisasi Petani Milenial Terhadap Pengembangan Pertanian Kota Palopo - Baharuddin Baharuddin; Annas Boceng; Hamja Abdul Halik (AGROVITAL : Jurnal Ilmu Pertanian, 2024)
The increasing role of the millennial generation in the economy, but there are still very few who become farmers, and the strengthening of the role of digitalization plus the role of the agricultural sector which continues to grow positively during this period is a strong signal for the improvement of the agricultural sector through agricultural digitalization efforts and encouraging the millennial generation to become farmers. The basic method of this research uses two approaches, namely the qualitative method. The qualitative approach referred to here is descriptive research, descriptive research is defined as research that only shows an image, description or details about the phenomenon/object being studied. From the results of the research located in South Wara District, that the millennial generation plays an important role in the agricultural sector to continue income and the economy and especially in the agricultural sector is advancing in the current pace of globalization. Increasing the interest of the millennial generation in the progressive agricultural sector is very important. Efforts to motivate the millennial generation as a driving force to support and improve agriculture. In this case, the change in the demographic structure seems to be less favorable and the millennial generation's lack of interest in the agricultural sector.